Obstacles to the Training Process for Ministry of Education Trainers from the Point of View of Primary School Teachers in the Center of Erbil Governorate - Osman Abdullah Hama Amin; Aram Gharib Qadir (Zanco Journal of Human Sciences, 2025)
This study aims to identify obstacles in the training process for trainers of the Ministry of Education from the perspective of primary school teachers in the heart of Erbil Province. To achieve this, a descriptive analytical approach was used, and the researchers used questionnaires as a research tool consisting of (40) paragraphs (5) distributed in areas (training course objectives, training environment, training course content, trainers, training methods and activities). After verifying the effectiveness and reliability of this tool, it was applied to a study sample that reached 2023-2024 gender teachers (444). As a result, the total degree of disability for in-service teacher training was "medium", the highest was "disability related to trainees" and the lowest was "disability related to training environment", indicating the existence of some disability facing the training course. The results also showed a statistically significant difference between the average of the study sample responses at a significance level (0.05) attributed to the variable (gender) and the favor of female teachers. The results also showed a statistically significant difference between the average of the study sample responses at a significance level (0.05) due to the variable (length of service) and in favor of (10) years of service or more.